2016
DOI: 10.3390/ijms17122089
|View full text |Cite
|
Sign up to set email alerts
|

Using CRISPR/Cas9-Mediated GLA Gene Knockout as an In Vitro Drug Screening Model for Fabry Disease

Abstract: The CRISPR/Cas9 Genome-editing system has revealed promising potential for generating gene mutation, deletion, and correction in human cells. Application of this powerful tool in Fabry disease (FD), however, still needs to be explored. Enzyme replacement therapy (ERT), a regular administration of recombinant human α Gal A (rhα-GLA), is a currently available and effective treatment to clear the accumulated Gb3 in FD patients. However, the short half-life of rhα-GLA in human body limits its application. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In order to investigate the functions of GLA and its therapeutic potential for FD, we performed CRISPR/Cas9-mediated gene editing to knock out expression of this gene in human embryonic stem cells (hESCs). The procedure was similar to that described in our previous work, where we established the GLA-null HEK293 cell line [8]. Briefly, the GLA -specific single-guide RNA (sgRNA) was designed by using Optimized CRISPR Design tool () to introduce the frameshift mutations in exon 1 of GLA gene as shown in Figure 1A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to investigate the functions of GLA and its therapeutic potential for FD, we performed CRISPR/Cas9-mediated gene editing to knock out expression of this gene in human embryonic stem cells (hESCs). The procedure was similar to that described in our previous work, where we established the GLA-null HEK293 cell line [8]. Briefly, the GLA -specific single-guide RNA (sgRNA) was designed by using Optimized CRISPR Design tool () to introduce the frameshift mutations in exon 1 of GLA gene as shown in Figure 1A.…”
Section: Resultsmentioning
confidence: 99%
“…The CRISPR/Cas9 with T2A-eGFP co-expression vector pSpCas9(BB)–2A-GFP (PX458) was a gift from Feng Zhang (Addgene plasmid). The exon 1 of GLA was selected for guiding RNA design and the sequence (5′-AGGAACCCAGAACTACATCT-3′) was cloned into PX458 (abbreviated as GLA-Cas9-GFP) as previously described [8]. The GLA -specific targeting plasmid was transfected into hESC line (WA09) by electroporation using Nucleofector System (Lonza, Basel, Switzerland) following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BTZ function could be influenced by its ability to increase autophagy [64,65] and lysosomal exocytosis [66], which could contribute to the better clearance effect in an α-Gal A independent manner. This argues for an extension of the range of applications to patients who carry variants that do not respond sufficiently to DGJ or who do not express any functional enzyme at all, for example in combination with ERT [67]. Despite therapeutic success in FD patients harboring the amenable p.N215S α-Gal A variant, in which it was also noted that lyso-Gb3 was reduced under treatment, chaperone treatment may not be sufficiently effective for all gene variants whose in vitro amenability is proven [61].…”
Section: Discussionmentioning
confidence: 99%
“…This study performed COL4A3 gene editing using CRISPR/Cas9 technology; we established a COL4A3 knockout mouse monoclonal cell line ( COL4A3 c.4852 insA p.Arg1618ThrfsX4) for result verification. Other studies using CRISPR/Cas9 editing have recently been published in several important studies in the field of kidney disease [22,23] : Using a CRISPR/Cas9-mediated gene knockout of GLA in HEK-293T cells provided a successful in vitro Fabry disease model, [24] and the CRISPR/Cas9 knockout of podocalyxin in podocyte-like cells [25] and conditional CRISPR/Cas9 in Drosophila garland cell nephrocytes found that reactive oxygen species formation might be a pathological mechanism of COQ2-nephropathy. [26] The gradual improvement of Cas9 technology could be quite useful in the advanced kidney research field.…”
Section: Discussionmentioning
confidence: 99%